2020
DOI: 10.21608/ejnf.2020.148120
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Performance of Growing Sheep Fed Silage of Salt Tolerant Plants Under South Sinai Conditions

Abstract: his experiment was conducted at Ras Sudr Research Station belonging to Desert Research Center to elucidate the effect of feeding salt tolerant plants (Atriplex nummularia, Fodder beet, Pearl millet) silage (STPS) on productive performance of male Barki sheep under arid and salinity conditions of Southern Sinai, Egypt. Sixteen male Barki sheep (31.42 ±1.79 kg and 4 months age) were randomly divided into two equal groups (8 each). The first group (control) was fed 40% berseem hay (BH) from total ration and serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
2
5
0
Order By: Relevance
“…Generally, animals fed control ration (BH) showed insignificant higher drinking and total water intake (ml/h/d) than those fed the other two tested rations (MSTP+PF and MSTP+Y). Such result was in corroboration with previous findings by Abo Bakr et al (2020a). On the other hand, animals fed ration based on BH (control group) recorded insignificant higher water balance value (2257 ml/h/d) than rations contained MSTP and supplemented with different feed additives (PF or Y) by 25.7 and 20.2 %, respectively Higher values of water balance were recorded by the control group (BH) which might be resulted as a consequence of higher water turnover rate and/or digest flow (Araújo et al, 2010).…”
Section: Water Utilizationsupporting
confidence: 93%
See 4 more Smart Citations
“…Generally, animals fed control ration (BH) showed insignificant higher drinking and total water intake (ml/h/d) than those fed the other two tested rations (MSTP+PF and MSTP+Y). Such result was in corroboration with previous findings by Abo Bakr et al (2020a). On the other hand, animals fed ration based on BH (control group) recorded insignificant higher water balance value (2257 ml/h/d) than rations contained MSTP and supplemented with different feed additives (PF or Y) by 25.7 and 20.2 %, respectively Higher values of water balance were recorded by the control group (BH) which might be resulted as a consequence of higher water turnover rate and/or digest flow (Araújo et al, 2010).…”
Section: Water Utilizationsupporting
confidence: 93%
“…Investigating economic efficiency (Table 10) pointed out to insignificant higher total gain in BH group (the control), while the higher cost of PF supplement (0.9 LE) was due to protected fat supplement negatively reflected on average return income. This result is consistent with Abo Bakr et al (2020a) showed feeding sheep on salt tolerant plants.…”
Section: Economic Evaluationsupporting
confidence: 92%
See 3 more Smart Citations